The impact of digital transformation on economic growth: A global evidence - Pham, Nang Thang; Vo, Tan Huy; Huynh, Le Giang; Nguyen, Mai Han (Journal of Finance - Marketing Research, 2025)
Digital transformation-driven economic growth is a key socio-economic development objective for many countries. This study explores the impact of digital transformation on economic growth across 77 countries, categorized into three income groups: high-income, upper-middle-income, and lower-middle-income countries, over the period from 2005 to 2022. The research employs an econometric approach based on the Cobb-Douglas production function to quantify the effects on economic growth, while the Generalized Method of Moments (GMM) estimation is utilized to address endogeneity concerns. The findings reveal that digital transformation plays a significant role in fostering economic growth. Countries that actively advance digital transformation initiatives tend to experience accelerated economic expansion. Additionally, fundamental economic drivers such as investment capital and labor also exert a positive influence on growth. The study further provides valuable policy insights to assist governments in formulating strategies to enhance economic development in an era of rapid global digitalization.